Characterizing Particle Board Made of Oil Palm Empty Fruit Bunch Using Central Composite Design - Lubis, Mirna Rahmah; Maimun, Teuku; Kardi, Jon; Masra, Rifdullah Bikri (Makara Journal of Science, 2018)
Particle boardwas made using processed oil palm empty fruit bunch and casein glue. This research used two factor variables and eight response variables to determine the best matrix/filler ratio and compression pressure for particle board production. The factor variables, (matrix/filler ratio and compression pressure), determined the response variables: modulus of rupture, water content, density, tensile strength,and both endothermic-and-exothermic temperatures and heats. This research aimedto optimize the mechanical and physical property of particle boards by using the bunch/glue ratio. The processing of data was undertaken by Response Surface Method (RSM) with Central Composite Design (CCD). The optimal conditions under which particle board created wereat matrix/filler ratio of 50:50 and compression pressure of 3.53 kg/cm2; resulting in a modulus of rupture of 325.32 kg/cm2, water content of 0.009%, density 0.826 g/cm3, and tensile strength of 2.573 kg/cm2. This research also indicates that casein glue results in particle board with optimum parameters of endothermic temperature of 247.74 °C, an endothermic heat of -4.122 mW, exothermic temperature of 431.08 °C, and exothermic heat of 7.526 mW. Based on physical testing, most particle board properties obtained fulfilled the standards of water content and density as required by the Indonesian National Standard/SNI 03-2105-2006.